Georges Lemaître primitive atom hypothesis - Falciano, Felipe Tovar; Fabris, Júlio César (Cadernos de Astronomia, 2023)
Georges Lemaître is a singular figure with important contributions to 20th century physics and cosmology. One of the pioneers in the elaboration of the primordial universe scenario, Lemaître was allegedly the first to interpret in depth the physical meaning of the observational results of Hubble’s team on the connection between the redshift of neighbouring galaxies and the expansion of the universe. Here we present a translation of the text published by Lemaître in 1949, in which he fully explains the idea that the universe arises from the disintegration of a "primitive atom". Using the characteristics of radiative processes, Lemaître develops a broad vision of the physical processes in the primordial universe that bears interesting similarities to what has now become the standard model of cosmology.